Impacto das emissões de poluentes gerados pelo corte a plasma de chapas metálicas - Merlini, Simone (2024)
The metalworking industry involves the transformation of metals into a product for following processes or into a product ready for the final consumer. One of the problems faced by the metalworking industry in the plasma cutting process is pollutant emissions. Pollutants generate impacts on the environment and also on the workplace itself, through emissions. With the use of machines and equipment, pollutants are emitted, generated during the sheet cutting process, to obtain smaller pieces. The main objective of this research is to measure the impact of pollutant emissions caused by plasma cutting of metal sheets in the metalworking industry. A methodological procedure organized in stages was developed, starting with the definition of the problem, followed by the operational and technical parameters, technical description of the pollutants, measurement of the impact, application of the measurement system and results and ending with the final considerations of the research. Furthermore, a bibliographical research was developed, based on selected and studied scientific articles and a description of the research scenario regarding the plasma cutting process of metal sheets. A qualitative and quantitative approach was used in the research. Using metrics designed for the impact factors of CO2, electricity, water and raw materials, it was possible to develop and analyze the impacts of pollutant emissions, where they are converted into production costs. And an analysis of each impact factor with the pillars of the sustainability tripod was developed. Finally, it is concluded that the impact on costs related to raw materials is greater compared to the impact on the costs of electricity, water and CO2. It is possible to verify the importance of using alternatives to reduce pollutant emissions in industries.